UTILIZATION OF ARECA NUT AS A CORROSION INHIBITOR AND ECOPRINT FABRIC MATERIAL BY THE SUKAKARYA VILLAGE WOMEN'S FARMING GROUP, MUSI RAWAS REGENCY, SOUTH SUMATRA - Putra, Erwin Hendra; Erwin, Erwin; Prayoga, Dedo Kevin (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
PT Pertamina EP Pendopo Field, within the GEMILANG (Movement for Women to Preserve Nature through Areca Nut Conservation) program, has successfully empowered the women of Sukakarya Village by promoting the cultivation and utilization of the abundant areca nut trees in the area. As beneficiaries of the GEMILANG program, the Melati Women's Farming Group (KWT Melati) has successfully produced health products from areca nuts, such as ginger areca nut tonic (bandrek) and areca nut juice. Since the program's inception in 2020, KWT Melati has become more productive, engaging in vegetable cultivation and organic fertilizer production using areca nut waste. As the program has grown, GEMILANG has become increasingly inclusive, involving more women from Sukakarya Village. New initiatives under GEMILANG now include the development of areca nuts as a corrosion inhibitor for the industrial sector, using areca nut waste in fabric production through eco-printing techniques, and exporting areca nuts.